Designing Engaging Interactive Animatronics: Strategies and Implementation Insights - Netra M. Deshpande; Krishna T. Madrewar (International Journal of Optical Innovations & Research, 2024)
The field of animatronics uses robotic systems to imitate realistic movements and activities in mechanical figures. To enhance the recognition and performance of the animatronic as a relationship mediator, it is important that the animatronics in recreational games be perceived as human companions to create productive interaction scenarios. This study describes the design and implementation of a Java- based programming method, an Adriano microcontroller, an open environment, a depth camera (Carmine by Prime Sense), and human recognition of an electric dragon. A person's approximate skeletal data was discovered using information from the depth camera. The programme will monitor one or more people within the camera's field of view based on how the event moves. Among those observed, shared tasks were categorised as private. It has numerous realistic effects, such as sound, movement, and all different kinds of human and dragon joints. Further investigation into the efficacy of interactive content in the learning environment will be made possible by this animatronic design.
Keywords: Animatronics; MATLAB; Microcontroller; Multichannel servo controllers; Neural network; facial pose